Biocompatible Cubic Boron Nitride: A Noncytotoxic Ultrahard Material. (13th October 2020) - Yang, Jason H. C.; Teii, Kungen; Chang, Chung‐Chueh; Matsumoto, Seiichiro; Rafailovich, Miriam
Abstract: Cubic boron nitride ( c ‐BN) has an ultrahardness and a large bandgap energy like diamond. In the last 30 years, most of the attention has been directed towards the mechanical and electronic applications of c ‐BN, while its biological potential has been overlooked. The authors report in vitro biocompatibility of high‐quality c ‐BN films prepared by plasma‐enhanced chemical vapor deposition using the chemistry of fluorine. c ‐BN films become superhydrophilic when chemical‐treated in hydrogen and nitrogen plasmas with or without the impact of low‐energy ions due to a marked increase in polar part of the surface free energy by removal of the fluorine atoms terminating c ‐BN surfaces. Satisfactory proliferation and differentiation of osteoblastic cells comparable with a control sample and a superhydrophilic nanocrystalline diamond film, and the formation of mineral deposits by biomineralization are confirmed on the superhydrophilic c ‐BN films with negative values of zeta potential. The results demonstrate a high potential of c ‐BN as a noncytotoxic ultrahard coating material for biological and biomedical applications. Abstract : Cubic boron nitride ( c ‐BN) has an ultrahardness and a large bandgap energy similar to diamond, but its biological potential has been overlooked. This is the first report on the biocompatibility of high‐quality, superhydrophilic c ‐BN films through an in vitro cytotoxicity assessment. The results advance novel applications of c ‐BN for biomedical coatings and devices.